A GMRT 150 MHz search for variables and transients in Stripe 82. Issue 4 (21st October 2019) - Hajela, A; Mooley, K P; Intema, H T; Frail, D A
ABSTRACT: We have carried out a dedicated transient survey of 300 deg 2 of the SDSS Stripe 82 region using the Giant Metrewave Radio Telescope (GMRT) at 150 MHz. Our multi-epoch observations, together with the TGSS survey, allow us to probe variability and transient activity on four different time-scales, beginning with 4 h and up to 4 yr. Data calibration, RFI flagging, source finding, and transient search were carried out in a semi-automated pipeline incorporating the SPAM recipe. This has enabled us to produce superior-quality images and carry out reliable transient search over the entire survey region in under 48 h post-observation. Among the few thousand unique point sources found in our 5σ single-epoch catalogues (flux density thresholds of about 24, 20, 16, and 18 mJy on the respective time-scales), we find <0.08 per cent, 0.01 per cent, <0.06 per cent, and 0.05 per cent to be variable (beyond a significance of 4σ and fractional variability of 30 per cent) on time-scales of 4 h, 1 d, 1 month, and 4 yr, respectively. This is substantially lower than that in the GHz sky, where ∼1 per cent of the persistent point sources are found to be variable. Although our survey was designed to probe a superior part of the transient phase space, our transient search did not yield any significant candidates. The transient (preferentially extragalactic) rate at 150 MHz is therefore <0.005 on time-scales of 1 month and 4 yr, and <0.002 on time-scales of 1 d and 4 h, beyond 7σ detection threshold. We put these results in perspective with the previous studies and give recommendations for future low-frequency transient surveys.